Association of Depression and Anxiety With Expectations and Satisfaction in Foot and Ankle Surgery. Issue 16 (15th August 2021) - Henry, Jensen K.; Barth, Kathryn; Cororaton, Agnes; Hummel, Amelia; Cody, Elizabeth A.; Mancuso, Carol A.; Ellis, Scott
Abstract : Introduction: Mental health diagnoses involving depression or anxiety are common and can have a dramatic effect on patients with musculoskeletal pathologies. In orthopaedics, depression/anxiety (D/A) is associated with worse postoperative patient-reported outcomes. However, few studies have assessed the effect of D/A on expectations and satisfaction in foot and ankle patients. Methods: Adult patients undergoing elective foot and ankle surgery were prospectively enrolled. Preoperatively, patients completed the eight-item Patient Health Questionnaire Depression Scale, Generalized Anxiety Disorder Screener-7, Foot and Ankle Outcome Score (FAOS), and Expectations Survey. At 2 years postoperatively, surveys including satisfaction, improvement, and fulfillment of expectations were administered. Fulfillment of expectations (fulfillment proportion) and FAOS scores were compared between patients with D/A and non-D/A patients. Results: Of 340 patients initially surveyed, 271 (80%) completed 2-year postoperative expectations surveys. One in five patients had D/A symptoms. Preoperatively, D/A patients had greater expectations of surgery ( P = 0.015). After adjusting for measured confounders, the average 2-year postoperative fulfillment proportion was not significantly lower among D/A compared with non-D/A (0.86 versus 0.78, P = 0.2284). Although FAOS scores improved postoperatively for both groups, D/A patients had significantly lower preoperative and postoperative FAOS scores for domains of symptoms, activity, and quality of life ( P < 0.05 for all). D/A patients reported less improvement ( P = 0.036) and less satisfaction ( P = 0.005) and were less likely willing to recommend surgery to others ( P = 0.011). Discussion: Patients with D/A symptoms had higher preoperative expectations of surgery. Although D/A patients had statistically similar rates of fulfillment of expectations compared with non-D/A patients, they had markedly lower FAOS scores for domains of symptoms, activity, and quality of life. D/A patients also perceived less improvement and were more often dissatisfied with their outcomes. These findings should not dissuade providers from treating these patients surgically but rather emphasize the importance of careful patient selection and preoperative expectation management. Level of Evidence: Level III; retrospective review of prospective cohort study